Influencia del deficiente soporte familiar en el autocuidado de los adultos mayores de la estrategia sanitaria nacional de no transmisibles del hospital Pacasmayo en el año 2017. - Escobar Gallardo, Alicia (2017)
The present research work of descriptive type, was developed in 2017, through the sample formed by 26 seniors who are part of the National Sanitary Strategy of Non-Communicable Pacasmayo Hospital, located in the District of Pacasmayo Province Of Pacasmayo. This research report was made with the purpose of determining the influence of poor family support in the elderly care self care, since it allows us to identify which situations affect positively or negatively the physical, emotional and social well-being of the adult higher. The applied methodology was based on the inductive methods - analytical, synthetic and statistical methods and allowed us to interpret, study, organize and analyze the forms of support offered to the elderly and the perception of them about self care. The techniques and instruments used allowed to obtain the quantitative and qualitative data of the research group through observation, interview, survey and for the theoretical support the bibliographical compilation. The results obtained in this research confirm the hypotheses raised, since poor family support greatly influences elderly self-care, since the family favors physical, emotional and social well-being through greater adult communication Greater participation with people in their environment, greater participation within the group of Sanitary Strategy and adequate practices of the use of their leisure time.